Investigation of the relationship between Fusobacterium nucleatum presence and inflammatory mediator expression in Kazakhstani patients with colorectal cancer - Kulmambetova, Gulmira; Kurentay, Botakoz; Gusmaulemova, Alua; Bayanbek, Dina; Mamlin, Meiram; Khamzina, Saule; Shalekenov, Sanzhar; Kozhakhmetov, Arman (Frontiers in Microbiology, 2025)
ObjectivesFusobacterium nucleatum has been recognized as a critical microorganism contributing to the development and progression of colorectal cancer (CRC). However, the role of F. nucleatum in colorectal cancer, including its effects on immune factors and the tumor microenvironment, remains unclear. This study aimed to explore the relationship between the presence of F. nucleatum and the expression of inflammation-related genes (IL6, IL1B, IL10, IL17, TNF) in tumor and matched normal tissue of Kazakhstani CRC patients.MethodsThe abundance of F. nucleatum was detected in 113 paired tumor and normal tissue specimens by quantitative PCR technology (qPCR). The interleukin expression levels of cytokines (IL-6, IL-1β, IL-10, IL-17, TNF-α) were examined by TagMan droplet digital PCR technology (ddPCR). Finally, we investigated the potential associations between the molecular and clinicopathological characteristics of the samples and the abundance of F. nucleatum.ResultsThe relative abundance of Fusobacterium nucleatum was significantly higher in cancerous tissues compared to normal tissues. Moreover, the expression levels of IL-6 and IL-1β were significantly elevated in the cancer group. A strong correlation was also found between high levels of Fusobacterium nucleatum and increased expression of IL-17. In addition, increased levels of Fusobacterium nucleatum were significantly associated with histological grade II and III colorectal cancer tissues, as well as with certain clinical characteristics, including microsatellite instability (MSI), patient nationality, and processed meat intake (p < 0.05).ConclusionOur findings highlight the significance of Fusobacterium nucleatum and the alterations in gene expression associated with colorectal cancer. Investigating the microbial landscape and gene expression patterns in CRC patients could offer a valuable approach for enhancing screening techniques and developing effective therapeutic strategies.